ANTHROPOLOGICAL STUDY OF KERMAN CARPET SYMBOLS, SHAPES, AND DESIGNS - Sharbatian, Yaghoub; Bagheri, Roya (American International Journal of Social Science Research, 2021)
Different traditional Iranian art forms can be known as a single semantic recreation in different forms. All of them imply some shared concepts which are a mix of Persian and Islamic beliefs. These arts have a symbolic tone and the artist speaks through their art using the appropriate allegorical tools. In this field, the Kerman carpet should be known as an excellent manifestation of symbols and mysterious designs that are eloquently implemented on the carpet. The purpose of this study is the anthropological analysis of the symbols, designs, and patterns used in the Kerman carpet as well as the analysis of the Kermanian people's beliefs based on those designs and symbols. The research method used here is the Qualitative type and in the form of ethnographic, and also the information are collected using interview-participation and documents. The theoretical framework of this study is based on Clifford Geertz’s Symbolic-Interpretive Anthropology Approach theory. The findings of this study show that the Kerman carpet alongside its beauty and charm includes meaningful designs and patterns and these designs and symbols are derived from the geographical-cultural and social area and are connected with the everyday life, traditions, and beliefs of the people of their area.